2005
DOI: 10.1210/jc.2005-2246
|View full text |Cite
|
Sign up to set email alerts
|

We All Remember Our First Kiss: Kisspeptin and the Male Gonadal Axis

Abstract: The year 2003 was witness to a friendly collision between the fields of cancer and reproduction when a little known G protein-coupled receptor (GPR54) was pushed into the limelight. GPR54 was first cloned from rat brain in 1999 (1), but was an orphan receptor until 2001, when several groups discovered a high affinity ligand (2)(3)(4). This ligand, metastin, is derived from the proteolytic processing of a parent protein called kisspeptin-1 (metastin 1-54 ϭ kisspeptin-1 68 -121). Metastin's name was so coined be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…This peptide has been credited with a regulatory role for the seasonal secretion of GnRH, possibly kisspeptin and gonadotrophins (Reiter, 1998;Seminara, 2005). Additionally, this hormone may exert a direct gonadal effect as indicated by the presence of its receptors in Leydig cells and seminiferous tubules (Karasek et al, 1990;Luboshitzky et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This peptide has been credited with a regulatory role for the seasonal secretion of GnRH, possibly kisspeptin and gonadotrophins (Reiter, 1998;Seminara, 2005). Additionally, this hormone may exert a direct gonadal effect as indicated by the presence of its receptors in Leydig cells and seminiferous tubules (Karasek et al, 1990;Luboshitzky et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Kisspeptin/GPR54 complex plays a critical role in the central regulation of the hypothalamo-pituitary gonadal axis on both male and female. 9,10 Exogenously administered kisspeptin evokes a stimulatory effect on gonadotropin secretion. 4 It is now well documented that peripheral and central (intracerebroventricular, ICV) administration of kisspeptin stimulates a dose-dependent rise in serum levels of gonadotropin in adult male rats.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that kisspeptin neurons are located upstream of GnRH neurons to stimulate LH release ( Seminara, 2005 ). Because the excitatory effect of kisspeptin on gonadotropin secretion is inhibited by GnRH antagonists ( Navarro et al, 2005 ), and as kisspeptin administration to hypothalamo-pituitary disconnected ewe models could not change LH concentration ( Smith et al, 2008b ), it has been concluded that kisspeptin acts at the hypothalamic level, not the pituitary, to stimulate GnRH release.…”
Section: Discussionmentioning
confidence: 99%